2004
DOI: 10.1128/jcm.42.12.5609-5613.2004
|View full text |Cite
|
Sign up to set email alerts
|

Direct Identification of Gram-Positive Cocci from Routine Blood Cultures by Using AccuProbe Tests

Abstract: Rapid and reliable identification of bacteria directly from blood cultures is important in clinical practice to guide appropriate antibiotic therapy. In this study, the performance of the AccuProbe (Gen-Probe, Inc., San Diego, Calif.) in direct identification of Staphylococcus aureus, Streptococcus pneumoniae, enterococci, and group A and B streptococci from positive blood culture bottles was evaluated by using 6-year routine clinical laboratory blood culture material from Päijät-Häme Central Hospital, Lahti, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…However, with the S. aureus probe, although the specificity was very high (99.8%) the sensitivity was quite low (72.4%). The cut-off values were adjusted and the performance of the tests, especially that for S. aureus, was significantly improved [61].…”
Section: Hybridization Techniques For Positive Blood Culturesmentioning
confidence: 99%
“…However, with the S. aureus probe, although the specificity was very high (99.8%) the sensitivity was quite low (72.4%). The cut-off values were adjusted and the performance of the tests, especially that for S. aureus, was significantly improved [61].…”
Section: Hybridization Techniques For Positive Blood Culturesmentioning
confidence: 99%
“…Recent improvements in blood culture processing have been made through the molecular detection of staphylococci, enabling rapid recognition of meticillin-resistant Staphylococcus aureus (Fujita et al, 2005). Broader-ranging molecular identification systems, such as gene hybridization and PCR-based probes, have been used to identify bacteria from machine-positive cultures, but these have yet to improve patient outcomes (Lindholm & Sarkkinen, 2004;Wellinghausen et al, 2004). Other developments in laboratory medicine such as increased reliance on digital reporting or telephone reports from a centralized diagnostic laboratory reduce the direct contact with the patient's attending physician and thus opportunities for result interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies report specificity of 100% but one center reported an accuracy of only 80.8% [120] compared with 99.8% in the other center [120]. The reasons for the differences are not clear and neither study reported outcome data associated with assay performance in their respective centers [120,121].…”
Section: Molecular Non-amplifiedmentioning
confidence: 95%
“…Two published studies on its use on positive BCs are available but with vastly different results [120,121]. Both studies report specificity of 100% but one center reported an accuracy of only 80.8% [120] compared with 99.8% in the other center [120].…”
Section: Molecular Non-amplifiedmentioning
confidence: 98%